The diagnostic accuracy of abdominal ultrasound findings in patients evaluated for peripheral lymphadenopathy in a high HIV TB endemic population - Adams, Ellouise (Department of Medicine, 2024)
Background: Extrapulmonary tuberculosis (EPTB) is common among people living with HIV (PLWH). The abdominal ultrasound is an accessible investigation frequently employed to support the diagnosis of EPTB but may lead to misdiagnoses of diseases with overlapping clinical features, such as lymphoma. Objectives: To describe the abdominal ultrasound features and confirmed diagnoses of patients referred to a biopsy clinic with unexplained lymphadenopathy. Method: This was a retrospective descriptive study of patients attending the peripheral lymph node biopsy clinic at Groote Schuur Hospital (GSH) between 2017 and 2020 who had abdominal ultrasound examination while being investigated for unexplained lymphadenopathy. Ultrasound features were compared to the final diagnosis made on the lymph node biopsy. Results: Thirty-four patients were included, most of whom were HIV-infected (59.0%). Approximately one third had a confirmed diagnosis of lymphoma (29%) and approximately one third had a confirmed diagnosis of tuberculosis (32%). Splenic hypoechoic lesions were more common in patients with lymphoma (63.6%) than patients with tuberculosis (45.5%) and malignancy (16.7%). Ascites was equally distributed between patients with tuberculosis (36.4%) and lymphoma (36.4%). The ultrasound report and confirmed diagnoses were in agreement in 40.0% of patients with tuberculosis. Additionally, 36.4% of patients with confirmed lymphoma were suspected to have tuberculosis based on the abdominal ultrasound. Conclusion: Abdominal ultrasound detection of abnormalities such as splenic hypoechoic lesions, lymphadenopathy and ascites/pleural effusion have a differential diagnosis including both tuberculosis and lymphoma, and should be interpreted in conjunction with equally focused diagnostic tests.